Evaluation of ocular manifestations and its predictors in dengue patients in Hospital Selayang - Bakar, Farah Abu (2018)
Background: Dengue is the most rapidly spreading mosquito-borne disease in the world causing a substantial public health burden in the Western Pacific Region. It is a major cause of mortality and morbidity in Malaysia. Malaysia is hyperendemic for dengue, as evidenced by simultaneous presence of all four dengue serotypes (DENV-1, DENV-2, DENV-3, DENV-4). However, the predominant serotype differs from year to year and varies across the different states in Malaysia. Dengue fever has a wide spectrum of clinical manifestations with varying degrees of severity. Different dengue serotypes may contribute to the variability and severity of manifestations. Over the recent years, there has been increasing numbers of cases of ocular manifestations in dengue, from mild selflimiting presentation to sight threatening conditions. Objectives: The objectives of this study are to determine the prevalence of ocular manifestations in dengue patients, to determine the association between ocular manifestations and the different serotypes of dengue virus and to identify the predictors of ocular manifestations in dengue. Methods: This is a cross-sectional study conducted in Hospital Selayang, Gombak, Malaysia. One hundred and thirty eight patients diagnosed with dengue fever were recruited from January 2017 to January 2018. Complete ocular examination was done for each patient including assessment of macula thickness using Heidelberg Spectral-Domain Optical Coherence Tomography (OCT). Serum blood sample is sent for full blood count and dengue serotype. Reverse transcription- polymerase chain reaction (RT-PCR) method was used to identify the dengue serotypes DENV-1, DENV-2, DENV-3 and DENV-4. Findings were analysed using Statistical Package for Social Sciences (SPSS) comparing ocular manifestations among the different dengue serotypes. Results: Ocular manifestations were present in 18 (13%) patients from the study. Fourteen (10%) patients had eye redness. Subconjunctival haemorrhage was the commonest eye findings seen in 14 patients in which 9 (64%) patients were infected by DENV-1 (p=0.019). Fundus findings were present in 3 patients including 2 maculopathy. One patient had anterior uveitis and is found to be associated with DENV-3 (p= 0.014)Age, gender, ethnicity and full blood count values including platelet level were found not to be significant predictors in this study (p>0.05). Conclusion: Ocular manifestations are prevalent amongst dengue patients. There is association between specific dengue serotype with ocular manifestations. There is no significant predictors of dengue ocular manifestation identified in this study. Further research and larger studies need to be conducted to evaluate correlation between the different serotypes with other types of ocular manifestation and its severity.